The Theories of Makki and Madani According to Classical and Contemporary Scholars - Khoyumatul Kiftiyah; Wahidah Wahidah; Muslimah Muslimah (CV. Creative Tugu Pena, 2023)
This study aims to describe the study of Makki and Madani theories according to classical and contemporary scholars. This research used library method, which is done by reading relevant literature sources to obtain the necessary data. Sources of data are printed and electronic books and journals. Data analysis was carried out in a related and continuous manner until the study was completed, through the steps of data collection, data reduction, then presenting the data descriptively and the explanation above, there are several things that can be concluded that: the concept of Makki-Madani in the view of classical scholars is based on three things, namely: time, place and target, although it is still a debate to be updated as did Nasr Hamid Abu Zaid; The determination of Makki and Madani also took into account the context of the reality of society at that time and the style of language used, because the socio-cultural conditions of the people of Mecca and Medina were slightly different. This assumption has been realized by classical and contemporary scholars with the terms inzar phase (Makkah) and the treatise phase (Medina), both of which have different emphases; Abu Zaid's anxiety has actually become a classical scholarly debate, but Abu Zaid is more critical in responding to it by using historical-scientific data and analysis; Understanding Makki and Madani theories is a necessity for a commentator to avoid ahistorical interpretations because they tend to cause errors in interpretation.. Keywords: Theory of Makki, Theory of Madani, Classical Scholars